Twin Attributes of Tyrosyl-tRNA Synthetase of Leishmania donovani: A HOUSEKEEPING PROTEIN TRANSLATION ENZYME AND A MIMIC OF HOST CHEMOKINE - Anand, Sneha (J Biol Chem, 2016)
Aminoacyl-tRNA synthetases (aaRSs) are housekeeping enzymes essential for protein synthesis. Apart from their parent aminoacylation activity, several aaRSs perform non-canonical functions in diverse biological processes. The present study explores the twin attributes of Leishmania tyrosyl-tRNA synthetase (LdTyrRS) namely, aminoacylation, and as a mimic of host CXC chemokine. Leishmania donovani is a protozoan parasite. Its genome encodes a single copy of tyrosyl-tRNA synthetase. We first tested the canonical aminoacylation role of LdTyrRS. The recombinant protein was expressed, and its kinetic parameters were determined by aminoacylation assay. To study the physiological role of LdTyrRS in Leishmania, gene deletion mutations were attempted via targeted gene replacement. The heterozygous mutants showed slower growth kinetics and exhibited attenuated virulence. LdTyrRS appears to be an essential gene as the chromosomal null mutants did not survive. Our data also highlights the non-canonical function of L. donovani tyrosyl-tRNA synthetase. We show that LdTyrRS protein is present in the cytoplasm and exits from the parasite cytoplasm into the extracellular medium. The released LdTyrRS functions as a neutrophil chemoattractant. We further show that LdTyrRS specifically binds to host macrophages with its ELR (Glu-Leu-Arg) peptide motif. The ELR-CXCR2 receptor interaction mediates this binding. This interaction triggers enhanced secretion of the proinflammatory cytokines TNF-α and IL-6 by host macrophages. Our data indicates a possible immunomodulating role of LdTyrRS in Leishmania infection. This study provides a platform to explore LdTyrRS as a potential target for drug development